2001
DOI: 10.4049/jimmunol.166.3.2041
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Dipeptidyl Peptidase IV (CD26) Suppresses Autoimmune Encephalomyelitis and Up-Regulates TGF-β1 Secretion In Vivo

Abstract: CD26 or dipeptidyl peptidase IV (DP IV) is expressed on various cell types, including T cells. Although T cells can receive activating signals via CD26, the physiological role of CD26/DP IV is largely unknown. We used the reversible DP IV inhibitor Lys[Z(NO2)]-pyrrolidide (I40) to dissect the role of DP IV in experimental autoimmune encephalomyelitis (EAE) and to explore the therapeutic potential of DP IV inhibition for autoimmunity. I40 administration in vivo decreased and delayed clinical and neuropathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
115
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 58 publications
6
115
2
Order By: Relevance
“…In indicated experiments, mice were immunized for a second time with 200 mg MOG peptide in CFA (Sigma-Aldrich) containing 800 mg killed M. tuberculosis (Sigma-Aldrich) 7 d after primary immunization. Mice were monitored daily for clinical signs of EAE and graded on a scale of increasing severity from 0 to 5, according to a previously published grading scale (26) and detailed in Supplemental Table I. Daily clinical scores were calculated as the average of all individual disease scores within each group.…”
Section: Induction and Clinical Evaluation Of Eaementioning
confidence: 99%
“…In indicated experiments, mice were immunized for a second time with 200 mg MOG peptide in CFA (Sigma-Aldrich) containing 800 mg killed M. tuberculosis (Sigma-Aldrich) 7 d after primary immunization. Mice were monitored daily for clinical signs of EAE and graded on a scale of increasing severity from 0 to 5, according to a previously published grading scale (26) and detailed in Supplemental Table I. Daily clinical scores were calculated as the average of all individual disease scores within each group.…”
Section: Induction and Clinical Evaluation Of Eaementioning
confidence: 99%
“…The CD26 molecule functions as the cell membrane-associated exopeptidase dipeptidyl peptidase (DP) 4 IV (EC 3.4.14.5), an enzyme capable of cleaving N-terminal dipeptides from polypeptides with either proline or alanine residues at the penultimate position (1)(2)(3). Many recent reports have demonstrated that CD26/DP IV serves as an important regulator of immune responses by affecting T cell activation, proliferation, and cytokine production (1)(2)(3)(4)(5)(6)(7)(8). Subsequently, multiple roles were predicted for CD26/DP IV in leukocyte homing and inflammation.…”
mentioning
confidence: 99%
“…Notably, many ligands engaging membrane CD26/DP IV at the T cell surface can efficiently induce the regulatory cytokine TGF-␤1 in T cells and inhibit T cell activation and DNA synthesis (8,19,23). Thus, we and others have shown that inhibition of CD26/DP IV activity on human or mouse T cells by synthetic or naturally occurring inhibitory ligands results in TGF-␤1-mediated suppression of IL-2 and IFN-␥ production, as well as in suppression of T cell proliferation in vitro (4,8,19,23).…”
mentioning
confidence: 99%
“…CD26 is also involved in T-cell activation, owing to its association with CD45, mannose 6-phosphate/insulin-like growth factor II receptor and adenosine deaminase (ADA) (Morimoto et al, 1989;Dang et al, 1990aDang et al, -d, 1991Torimoto et al, 1991;Kameoka et al, 1993;Morrison et al, 1993;Ikushima et al, 2000). Additionally, its DPPIV enzyme activity has a key role in various aspects of T-cell activation, as demonstrated by studies using DPPIV inhibitors, soluble CD26/DPPIV molecules or CD26 genetic mutants (Flentke et al, 1991;Tanaka et al, 1993Tanaka et al, , 1994Steinbrecher et al, 2001). Besides its involvement in normal T-cell function, CD26 may also have a role in the development of certain tumors (Tanaka et al, 1995;Stecca et al, 1997;Bauvois et al, 1999;Dang and Morimoto, 2002).…”
mentioning
confidence: 99%